EVALUASI ASPEK LINGKUNGAN TEBING BREKSI MENGGUNAKAN INDIKATOR SUSTAINABLE TOURISM UNWTO - Andreas Yogi Prasetyo (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Endowed with stunning natural beauty, Sleman has become a destination increasingly flooded by tourists from year to year. The rapid development of tourism does have a positive impact, especially on the economic side, but on the other hand, it can have a negative impact if the management does not prioritize the principles of sustainable tourism. The type of tourism that can be affected is tourism that relies on nature as its main attraction, Cliff of Breksi is one of them. Cliff of Breksi has experienced rapid development in terms of the number of tourist visits, but it has never been examined whether its management is following the principle of sustainability. The objectives of this research are: a) to identify the management of the environmental aspects of Cliff of Breksi, whether it is following the indicators of sustainable tourism from The World Tourism Organization (UNWTO) and b) determine what things need to be improved so that management can be more optimal. The research method used is a descriptive qualitative method. Research data were collected through in-depth interviews and observations. The results of the study indicate that the manager has so far had awareness and understanding in applying the principles of sustainable tourism as in the indicators of UNWTO sustainable tourism.Keywords: evaluation of nature tourism, indicator, sustainable tourism